Perencanaan Arus Kas Terhadap Peningkatan Profitabilitas Unit Pengelola Kegiatan Dana Amanah Pemberdayaan Masyarakat Mutiara Abadi - Puji Mulyati; Indra Hastuti; Esti Dwi Rahmawati; Evi Elisanti (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
. The purpose of this study was to determine the effect of planning on increasing profitability at UPK DAPM Mutiara Abadi, Boyolali Regency. The method used in this research is descriptive qualitative method. The research object is UPK DAPM Mutiara Abadi, Boyolali Regency, which is a company engaged in the economic empowerment of rural communities. The effect of this cash planning precisely is to set achievement targets. The realization of the cash flow budget is a way of how this planning can be achieved. The results showed that the UPK DAPM Mutiara Abadi, Boyolali Regency, in planning and realizing cash flows was relatively appropriate in its implementation so that all the targeted profit plans were achieved. This is evidenced by the achievements in 2018 – 2022, all profit targets always experience a plus deviation.